Characterization of Patients with Central Nervous System Infections - Benigno Figueiras Ramos; Ángel Julio Romero Cabrera; Raúl López Fernández; Sandra Borroto Lecuona; Raúl Nieto Cabrera (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Background: Central nervous system infections tend to present specific characteristics according to their clinical form and the causative agents that produce them. Objective: To characterize patients with central nervous system infections. Methods: Descriptive case series study conducted at the General University Hospital "Dr. Gustavo Aldereguía Lima'', in Cienfuegos. Patients with central nervous system infections were analyzed from January 2002 to December 31st, 2006. Variables such as age, sex, duration of stay at hospital, date of their stay, clinical manifestations, tests used for diagnosis, predisposing conditions, most common germs and final outcome. Results: The average age of patients was 35.65 years old. Females were predominant. Average stay time was 5 days. Out of the total, 22 patients died (6.9%), mainly due to bacterial meningoencephalitis being lymphocyte meningoencephalitis the most frequent. The most affected age group was that from 20 to 29 years old. From July to October there was a higher incidence of lymphocytic meningitis. From January to December bacterial meningoencephalitis was predominant. The most frequent symptoms and signs were headache (92.1%), fever (82.7%), meningism (67.6%) and vomiting (37.7%). The clinical method and the study of the cerebrospinal fluid were the most widely used methods for diagnosis. The predisposing factors were pneumonia, sinusitis and alcoholism. S. pneumoniae was the most frequently isolated microorganism while E. Coli caused the highest mortality rate. Conclusions: symptoms like fading consciousness (OR = 41.735), purpuric lessions (OR = 6.641) or bacterial meningoencephalitis (OR = 22.958) were independently associated with the risk of dying.